PENGARUH PENERAPAN PROBLEM BASED LEARNING DENGAN MEDIA CHEMIMAGZ TERHADAP HASIL BELAJAR SISWA PADA MATERI HIDROKARBON - Rizkia Hasanah; Lisa Utami (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2020)
AbstractThis research was instigated by the low of  student chemistry learning achievement at the eleventh grade of MIPA of State Senior High School 3 Dumai. Therefore, it was conducted an Experimental research with pretest and posttest design. This research aimed at knowing the effect of implementing Problem Based Learning model with Chemimagz media toward student learning achievement on Hydrocarbon lesson. The subjects of this research were the eleventh-grade students of MIPA in the Academic Year of 2017/2018. The samples of this research were the eleventh-grade students of MIPA 1 as the Experimental group and the students of MIPA 2 as the Control group. The data in this research were collected by using observation, preliminary data test that was homogeneity test, final data tests that were pretest and posttest, and documentation. Kp formula was used to know the effect of implementing the model toward learning achievement. The difference effect was analyzed by using Paired Sample t-test. Based on the data analysis of preliminary and final data, it was obtained that tobserved was 2,267 and ttable was 2,002 at 5% significant level. tobserved was higher than ttable, so H0 was rejected and Ha was accepted. It meant that there was an effect of impelenting Prblem Based Learning model with Chemimagz media toward student learning achievement on Hydrocarbon lesson at the eleventh grade of MIPA of State Senior High School 3 Dumai, and the effect was 8,27%.Keywords: Learning Achievement, Problem Based Learning, Chemimagz, Hydrocarbon